Regional restructuring in planktic foraminifera communities through Pliocene-early Pleistocene climate variability - Ekaterina Larina; Adam Woodhouse; Anshuman Swain; Christopher M. Lowery; Rowan C. Martindale; Corinne E. Myers (Nature Communications)
Abstract Recent studies highlight asymmetrical range shifts within plankton due to spatial variability in climate change, impacting marine ecosystem functioning and biogeochemical cycling. The Pliocene—early Pleistocene interval, characterized by significant climatic fluctuations, provides a framework to study regional responses of marine organisms, such as planktic foraminifera. Using bipartite network analysis of the Triton database, we investigate biogeographic shifts in macroperforate planktic foraminifera ecogroups, tracking taxonomic diversity and distribution. Here we show high turnover between symbiont-bearing warm-water and high-latitude dwellers, isolated to the North Atlantic, and an expansion of cold-water subthermocline taxa across basins, particularly in the South Pacific. Enhanced water column stratification and nutrient export to mesopelagic depths, associated with the intensification of the Northern Hemisphere Glaciation, likely drove shifts in species diversity and ecogroup latitudinal gradients toward modern patterns. This localized community restructuring emphasizes the importance of regional to hemispheric heterogeneity in understanding biodiversity responses to future climate change.